Estudio flujo-presión de la micción en el hombre - Pablo Valdevenito S., Juan (Revista Hospital Clínico Universidad de Chile, 2007)
Pressure-flow study of voiding is, at present, the best method of analysing voiding function quantitatively. It is an invasive second line study by which the relationship between pressure in the bladder and urine flow is measured during bladder emptying. The main use of it is the evaluation of older men with lower urinary tract symptoms. It allows to differentiate between patients with low urinary flow resulting from poor bladder contractility (low detrusor pressure) and those whose low urinary flow is secondary to true bladder outlet obstruction (high detrusor pressure), as well as combined alterations. In this article we describe the International Continence Society (ICS) nomenclature, the bladder detrusor and urethral functions during voiding, as well as some principles of voiding mechanics. We also discuss the analysis of the results in men with bladder outlet obstruction using the Abrams-Griffiths nomogram, the Schäfer nomogram and the ICS nomogram, including the evaluation of bladder contractility